Marketing Digitalization in Micro, Small, and Medium Enterprises (MSMEs) of Pamekasan Regency in Post-Pandemic - Rahman, Fadali; Sudarmiatin, Sudarmiatin; Hermawan, Agus (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Digitalization is a process of moving a business model that was originally used manually toward digital. While digital marketing or digital marketing is a form of business promoting and marketing a brand or brands using digital media such as the internet. The purpose of this study was to find out the use of digital marketing in post-pandemic Pamekasan Regency SMEs. This research method uses descriptive quantitative analysis with data collection techniques using a questionnaire. Respondents in this study were Pamekasan Regency MSMEs engaged in the food and beverage sector with a total sample of 45 MSMEs. The data analysis process uses editing, coding, tabulation, and data analysis.